Peran Guru BK dan PAI Dalam Menyikapi Kasus Bullying di SMPN 08 Palembang - Aulia Azzahra; Winda Andini; Ani Marlia; Alvina Mei Khasanah; Annisa Ayu Sabrila; Maulina Safitri; Ayu Enggar Wahyuni; Muhammad Rivaldo Ferdiansyah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Bullying is a serious issue that can have detrimental effects on victims, both physically and psychologically. In this digital era, bullying cases are becoming increasingly complex and harmful to many students. Therefore, this research is essential to understand the causes and impacts of such behavior. The research method employed in this article is qualitative, with a descriptive approach. Data collection methods include interviews, observations, and documentation. The data analysis technique involves several stages, namely data collection, data presentation, and drawing conclusions. Based on the results and discussions related to the roles of Guidance and Counseling (BK) and Islamic Education (PAI) teachers in responding to bullying incidents at SMPN 8 Palembang, it was found that the school has established regulations and policies to prevent bullying cases. A deep understanding of the bullying phenomenon has been gained by the school, acknowledging that bullying can take various forms, including direct physical contact, direct verbal contact, direct non-verbal behavior, indirect non-verbal behavior, and sexual harassment. Bullying perpetrators tend to form groups with specific roles such as the bully, assistant bully, behavior reinforcer, defender, and outsider. Several factors that can trigger bullying cases involve individual, family, peer, internal, and external factors. The impacts of bullying behavior encompass both psychological and physical consequences. In the efforts to prevent and handle bullying cases, schools play a crucial role. They have established regulations aimed at preventing bullying incidents within the school environment. Awareness of various forms of bullying and understanding the roles of individuals within bullying groups assist schools in designing more effective prevention strategies.